Viscosity reduction of Ricinus communis L. (MAMONA) biodiesel by chemical acetylation - Silva, Carmem Cícera Maria da; Moraes, Leila Cristina Konradt; Santos Júnior, José Ribeiro dos; Castro, Thiago Luis Aguayo de (Brazilian Journal of Production Engineering, 2021)
Castor seed oil (Ricinus communis L.) is used for biodiesel production due to its resistance and the fact that it does not compete with food production, however a high concentration of ricinoleic acid in its chemical composition gives the oil of R. communis some atypical characteristics, such as high viscosity. Therefore, this research aimed to analyze an acetylation reaction of ricinoleic esters as an alternative to reduce the viscosity of R. communis biodiesel. The oil from the seeds and R. communis was elegant and transesterified by two methods (A with 30 minutes and B with 60 minutes), where the reaction time is differentiated and after that the two types of biodiesels were acetylated. The physicochemical tests of the oil and biodiesel and 1H and 13C NMR of the oil and acetylated biodiesel were carried out. The physical-chemical properties of the specifications, with the exception of density and viscosity. An analysis by 1H and 13C NMR showed a major presence of ricinoleic acid in the oil of R. communis and proved the efficiency of the acetylation reaction. Acetylation reduced viscosity by 30.45% in method A and 32.66% in method B. Chemical acetylation is an alternative for reducing the viscosity of R. communis biodiesel.